Ultra‐strong phosphorescence with 48% quantum yield from grinding treated thermal annealed carbon dots and boric acid composite. Issue 2 (10th November 2021) - Li, Qijun; Zhao, Zhenxiao; Meng, Shuai; Li, Yuchen; Zhao, Yunyang; Zhang, Bohan; Tang, Zikang; Tan, Jing; Qu, Songnan
Abstract: Metal‐free room‐temperature phosphorescence (RTP) materials are of great significance for many applications; however, they usually exhibit low efficiency and weak intensity. This article reports a new strategy for the preparation of a high‐efficiency and strong RTP materials from crystalline thermal‐annealed carbon dots (CDs) and boric acid (BA) composite (g‐t‐CD@BA) through grinding‐induced amorphous to crystallization transition. Amorphous thermal‐annealed CDs and BA composite (t‐CD@BA) is prepared following a thermal melting and super‐cooling route, where the CDs are fully dispersed in molten BA liquid and uniformly frozen in an amorphous thermal annealed BA matrix after super‐cooling to room temperature. Upon grinding treatment, the fracture and fragmentation caused by grinding promote the transformation of the high‐energy amorphous state to the lower energy crystalline counterparts. As a result, the CDs are uniformly in situ embedded in the BA crystal matrix. This method affords maximum uniform embedding of the CDs in the BA crystals, decreases nonradiative decay, and promotes intersystem crossing by restraining the free vibration of the CDs, thus producing strong RTP materials with the highest reported phosphorescence quantum yield (48%). Remarkably, RTP from g‐t‐CD@BA powder is strong enough to illuminate items with a delay time exceeding 9 s. Abstract : We present a new grinding‐induced amorphous‐to‐crystalline transition method for the preparation of crystalline carbon dots (CDs) and boric acid (BA) composite (g‐t‐CD@BA), that exhibits a world‐record phosphorescence efficiency of 48% and ultra‐strong RTP. Remarkably, the intense green phosphorescence of the g‐t‐CD@BA can illuminate items for more than 9 s to the unaided eye.